Evaluation on nutritional components and nutritive quality in body of young fish Alosa sapidissima cultured in two different patterns - LIU Yongshi; JIANG Fei; SHI Yonghai (浙江大学学报. 农业与生命科学版, 2020)
In order to understand the effects of different culture patterns on the nutritional components of fish body, young fish Alosa sapidissima cultured in outdoor and shaded ponds were analyzed by biochemical analysis method, and the nutritive quality was analyzed and compared. The results showed that the body water content of shaded pond group (69.22%) was significantly lower than that of the outdoor pond group (70.68%) (P＜0.05), while the body crude fat content of shaded pond group (10.79%) was significantly higher than that of the outdoor pond group (7.48%) (P＜0.05). No significant differences in the contents of crude protein and ash in body were found between the two groups (P＞0.05). A total of 18 kinds of amino acids were found, and there were no significant differences in the contents of 11 kinds of amino acids (threonine, glycine, valine, methionine, tyrosine, phenylalanine, histidine, arginine, proline, tryptophane, cystine) between the two groups (P＞0.05), while in other seven kinds of amino acids (aspartate, serine, glutamic acid, alanine, isoleucine, leucine, lysine), the contents of outdoor pond group were significantly higher than those in shaded pond group (P＜0.05). The percentage contents of total amino acid (TAA), non-essential amino acid (NEAA) and delicious amino acid (DAA) in dry body of outdoor pond group were significantly higher than those of shaded pond group (P＜0.05), while there were no significant differences in the percentage contents of essential amino acid (EAA) and half-essential amino acid (HEAA) in dry body between the two groups (P＞0.05). There were no significant differences in the ratios of EAA/TAA, EAA/NEAA and DAA/TAA, and the body essential amino acid indexes (EAAI) of shaded pond group and outdoor pond group were 76.49 and 76.46, respectively. The total content of saturated fatty acid (SFA) of outdoor pond group (35.91%) was significantly higher than that of shaded pond group (27.70%) (P＜0.05), while the total content of poly-unsaturated fatty acid (PUFA) of outdoor pond group (13.66%) was significantly lower than that of shaded pond group (21.35%) (P＜0.05). There were no significant differences in the total contents of mono-unsaturated fatty acid (MUFA) and eicosapentaenoic acid+docosahexaenoic acid (EPA+DHA) between the two groups. The results indicated that the body protein quality of young fish A. sapidissima cultured in the outdoor pond was slightly better than that of young fish cultured in the shaded pond, but the body fatty acid quality of young fish A. sapidissima cultured in the shaded pond was much better. So, we suggest the composition of fatty acids in formulated feed should be optimized to increase the content of PUFA, especially the content of EPA and DHA.